2021
DOI: 10.20473/aijief.v4i2.31434
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Financial Technology Growth towards Inclusiveness of Unbankable Society in Achieving the Vision of the Islamic Banking Roadmap 2020-2025 (Case Study: Generation Z, Jabodetabek)

Abstract: Indonesia's digital economy continues to experience positive growth. The growth of the digital economy causes the volume of digital banking transactions to continue to increase. This shows the potential in utilizing the fintech market to the fullest. However, this market has not been utilized properly because there are still unbankable people who have not been accessed by banking services. The presence of fintech is expected to be a solution to target the unbanked population. Based on the existing potential, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…In 2020, Population Census survey shows the Indonesian population is dominated by Generation Z where there are 74.93 million people or 27.94% of Indonesia's total population of 270.2 million people. 68% of the majority of Generation Z in Indonesia are using digital payment apps to conduct daily transaction [14]. This data indicated that Generation Z is so important for the future growth of Indonesia.…”
Section: Generation Z In Indonesiamentioning
confidence: 94%
“…In 2020, Population Census survey shows the Indonesian population is dominated by Generation Z where there are 74.93 million people or 27.94% of Indonesia's total population of 270.2 million people. 68% of the majority of Generation Z in Indonesia are using digital payment apps to conduct daily transaction [14]. This data indicated that Generation Z is so important for the future growth of Indonesia.…”
Section: Generation Z In Indonesiamentioning
confidence: 94%
“…Research has indicated that their intention to use technology is crucial to the growth of the new financial technology industry (Dalimunte et al, 2019). According to data from the 2020 Population Census, Generation Z makes up the majority of Indonesians, making up approximately 74.93 million people, or 27.94% of the country's overall population of 270.2 million (Fadillah et al, 2021). The fastpaced advancement of technology in contemporary times has a noteworthy effect on the way of life of Generation Z, as they extensively depend on gadgets for numerous facets of their everyday routine.…”
Section: Generation Zmentioning
confidence: 99%
“…With the implementation of Laku Pandai, MSMEs will get additional fee-based income in addition to their daily core business. Ease of access through digitalization will foster Sharia financial inclusion from unbanka ble segmentation (Basrowi et al, 2020;Fadillah, 2021).…”
Section: Kata Kunci: Umkm Inklusi Keuangan Syariah Digitalisasi Ekono...mentioning
confidence: 99%